Biotechnological applications of industrially important amylase enzyme - SHIPRA DAS; SURENDRA SINGH; VINNI SHARMA; MANOHAR LAL SONI (International Journal of Pharma and Bio Sciences, 2011)
Amylases are digestive enzymes which hydrolyze glycosidic bonds in starch to glucose, maltose, maltotriose and dextrin. They have a lot of potential applications in both food and pharmaceutical industries. To improve the potential productivity of amylases, the organism genome must be modified and this is achieved in two ways: by (i) classical strain improvement by mutation and selection and (ii) the use of recombination Amylases are produced by microorganisms using submerged and solid state fermentation. However, solid state fermentation is attractive because of usage of cheap substrate, high yields and avoids substrate inhibition. This study reviews the microbial sources, strain improvement methods and fermentation characteristics of amylase production.